摆线针轮行星减速器CAD系统研究开发 - 汪冰 (Jixie chuandong)
The design calculation of cycloidal speed reducer is carried out by visual basic program language, and feature modeling of most of parts for the reducer is accomplished based on Pro/ENGIEER software. The parametric design and assembly design of the reducer are realized, and that design calculation and product model combine with nothing seam is also realized.